2002
DOI: 10.1002/jcb.10412
|View full text |Cite
|
Sign up to set email alerts
|

Role of testicular interstitial macrophages in regulating testosterone release in hyperprolactinemia

Abstract: Hyperprolactinemia-induced hypogonadism has been linked to a dysfunction of the hypothalamus-pituitary-testis axis. The direct inhibitory effects of prolactin on the testicular release of testosterone have also been demonstrated, though their mechanisms remain unclear. Incubation of rat testicular interstitial cells (TICs) with prolactin stimulated the release of testosterone. TICs from rats with anterior pituitary-grafting-induced hyperprolactinemia release lower amounts of testosterone than controls. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 54 publications
3
11
0
Order By: Relevance
“…This conclusion is consistent with the work of Huang et al (24). These investigators set out to explain the apparent paradox that PRL decreased testosterone in vivo while increasing its production from isolated Leydig cells in vitro, a paradox they were able to attribute to the intermediary role of interstitial macrophages and TNF-␣ production (24). Thus it is possible that both PRLs exert their common effects on testosterone biosynthesis via the testicular macrophage but their differential effects on apoptosis via PRL receptors on Leydig cells, spermatogonia, and elongated spermatids.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This conclusion is consistent with the work of Huang et al (24). These investigators set out to explain the apparent paradox that PRL decreased testosterone in vivo while increasing its production from isolated Leydig cells in vitro, a paradox they were able to attribute to the intermediary role of interstitial macrophages and TNF-␣ production (24). Thus it is possible that both PRLs exert their common effects on testosterone biosynthesis via the testicular macrophage but their differential effects on apoptosis via PRL receptors on Leydig cells, spermatogonia, and elongated spermatids.…”
Section: Discussionsupporting
confidence: 94%
“…The negative effect of hyperprolactinemia on testosterone production in adult animals therefore is in part direct and not only a consequence of reduced LH secretion. This conclusion is consistent with the work of Huang et al (24). These investigators set out to explain the apparent paradox that PRL decreased testosterone in vivo while increasing its production from isolated Leydig cells in vitro, a paradox they were able to attribute to the intermediary role of interstitial macrophages and TNF-␣ production (24).…”
Section: Discussionsupporting
confidence: 88%
“…Huang et al (1999Huang et al ( , 2001 found that hyperprolactinaemia in male rats diminished the response of Leydig cells, incubated with interstitial macrophages, to exogenous LH. This was due to high TNF-a production by macrophages during hyperprolactinaemia (Huang et al, 2003). Lower basal in vitro production of testosterone by WR Leydig cells occurred simultaneously with higher basal E 2 secretion.…”
Section: Discussionmentioning
confidence: 94%
“…(1999, 2001) found that hyperprolactinaemia in male rats diminished the response of Leydig cells, incubated with interstitial macrophages, to exogenous LH. This was due to high TNF‐α production by macrophages during hyperprolactinaemia (Huang et al. , 2003).…”
Section: Discussionmentioning
confidence: 99%
“…With a ribonuclease protection assay, expression of TGFβ1, IFNγ, and MIF was clearly demonstrated in the testis, whereas IL‐6, TNFα, and IL‐10 mRNAs were barely detectable using this approach, in spite of the fact that the production of at least IL‐6 and TNF‐α has been described in the adult testis (De et al, 1993; Syed et al, 1993). However, previous studies either used extremely sensitive methods such as reverse transcription—polymerase chain reaction or investigated synthesis and production in isolated cells or a combination of both rather than total testis (De et al, 1993; Xiong and Hales, 1993; Kern et al, 1995; Huang et al, 2003), suggesting that the sensitivity of the assay was insufficient to detect expression of low copy number cytokines in total testes RNA. Conversely, this also suggests that TGFβ1, IFNγ, and MIF are relatively highly expressed cytokines in the testis.…”
Section: Discussionmentioning
confidence: 99%